Healthcare Professionals’ Routine Practice Documentation And Its Associated Factors In Hospital - Almutiri, Bander Menawer Noor; alghamawi, Bandar ruddah; Firah, Ehab Nasruddin; Alotaibi, Faez Obaid Abdullah; Alkhudhayr, Osama Mohammed Jassim; Al-Otaibi, Abdullah Miteb; Al-Ghamdi, Omar Muhammad Gharam Allah; Ahmed Abed Aidah Al-Sufyani; Turki Mohammad N Almutairi; Khalid Sager H Alotaibi (Migration Letters, 2023)
Background: Proper documentation improves the continuity of patient care and enhances communication with the healthcare team. Documenting routine practice is significant for better diagnosis, treatment, continuity of care and medico-legal issues. However, healthcare professionals’ (HCP’s) routine practice documentation is poorly practiced. Therefore, this study aimed to assess healthcare professionals’ routine practice documentation and associated factors in hospital setting. Methods: An institution-based cross-sectional study design was used from January to April 2023. Self- administered questionnaire were used among 423 samples. SPSS version 28 software were used for data entry and analysis. Descriptive statistics and a logistic regression model were employed to describe the study subjects and to measure the strength of association between dependent and independent variables, respectively. A variable with a p value of <0.2 in bivariate logistic regression was considered for multivariable logistic regression. In multivariable logistic regression, ORs with 95% CIs and a p value of <0.05 were considered to determine the strength of association between dependent and independent variables. Results: Health professionals’ documentation practice was 51.1% (95% CI: 48.64 to 53.1). Lack of motivation (adjusted OR (AOR): 0.41, 95% CI: 0.22 to 0.76), good knowledge (AOR: 1.35, 95% CI: 0.72 to 2.97), taking training (AOR: 4.18, 95% CI: 2.99 to 8.28), using electronic systems (AOR: 2.19, 95% CI: 1.36 to[1] 3.28), availability of standard documentation tools (AOR: 2.45, 95% CI: 1.35 to 4.43) were statistically associated factors. Conclusions: HCPs’ documentation practice is good. Lack of motivation, good knowledge, taking training, using electronic systems and the availability of documentation tools were significant factors. Stakeholders should provide additional training, and encourage HCPs to use an electronic system for documentation practices.